‌‌+Hwty-nxt’s CHEST OF CANOPIC JARS - Mohsen Eltoukhy (Journal of the General Union of Arab Archaeologists, 2022)
[Ar] صندوق الأواني الكانوبية لجحوتي نخت يتناول البحث دراسة صندوق الأوانى الكانوبية الخاص بجحوتى نخت، من عصر الدولة الوسطى. عُثر على هذا الصندوق فى دير البرشا فى مصر الوسطى، وهي معروضة حالياً فى المتحف المصري تحت رقم CCG 4740. يهدف البحث إلى تحديد التعاويذ المقتبسة منها نصوص الصندوق عن طريق مقارنة هذه النصوص بمثيلاتها فى الكتب الدينية المختلفة (نصوص الأهرام – نصوص التوابيت – كتاب الموتى). هذا بالإضافة إلى وصف الصندوق والمناظر المصوره على جوانبه الداخلية يتبعها تعليقات على نمط الزخارف والنصوص المسجلة على جوانب الصندوق الخارجية والداخلية، وكذلك تأريخ الصندوق. [En] This article discusses a chest of Canopic jars belonging to +Hwty-nxt, during the Middle Kingdom. The chest was found at Deir El-Bersha in Middle Egypt and is preserved now under the number CCG 4740 in the Egyptian Museum. This article aims to identify the quoted spells by comparing its texts with other religious texts (Pyramid text, coffin text, Book of the Dead). A description of the chest of Canopic jars will be presented here, followed by general comments on the style, decoration and text painted on the interior of the chest. The article will also examine the dating of the chest, identification of its owner and the quoted spells.